Population-Based Study Detailing Cutaneous Melanoma Incidence and Mortality Trends in Canada - Conte, Santina; Ghazawi, Feras M.; Le, Michelle; Nedjar, Hacene; Alakel, Akram; Lagacé, François; Mukovozov, Ilya M.; Cyr, Janelle; Mourad, Ahmed; Miller, Wilson H.; Claveau, Joël; Salopek, Thomas G.; et al. (Frontiers in Medicine, 2022)
Background: Cutaneous melanoma (CM) is one of the most fatal types of skin cancer. Alarmingly, increases in incidence and mortality were noted globally for this malignancy, despite increase in understanding of melanoma pathogenesis and enhanced prevention efforts. Methods: Data was extracted for CM patients for provinces and territories (except Quebec) using two independent, population-based registries. Analysis was performed using both clinical and pathological characteristics: tumor morphologic classification, age, sex, anatomic site affected and place of residence. Mortality trends were assessed over a 7-year period. Results were compared to prior findings for 1992-2010. Results: During 2011-2017 39,610 patients were diagnosed with CM, with 5,890 reported deaths. National crude CM incidence was 20.75 (age-standardized incidence: 14.12) cases per 100,000 individuals per year. Females accounted for 45.8% of cases and 37.1% of deaths. While CM incidence rates continue to increase in both sexes, since 2013 the CM mortality is declining. We observed important differences across the provinces/territories, where Nova Scotia, Prince Edward Island, southern Ontario/British Columbia and certain coastal communities of New Brunswick demonstrated higher CM incidence and mortality rates. The observed incidence and mortality trends for 2011-2017 validate and extend earlier observations from 1992-2010 for CM. Conclusion: This population-based study highlights that while melanoma’s incidence is increasing in Canada, mortality rates are for the first time decreasing since 2013. We detail regional distribution of this cancer highlighting communities in southern/coastal areas, as being most at risk as well as the latest trends of melanoma incidence by age, sex and anatomic site. In males, melanoma is more common on the head/trunk, while in females on the extremities. Notably, Acral Lentiginous Melanoma was the only CM subtype that was more common in females, which primarily affects hands and feet.